2013
DOI: 10.1038/nrendo.2013.251
|View full text |Cite
|
Sign up to set email alerts
|

Consequences of excess iodine

Abstract: Iodine is a micronutrient that is essential for the production of thyroid hormones. The primary source of iodine is the diet via consumption of foods that have been fortified with iodine, including salt, dairy products and bread, or that are naturally abundant in the micronutrient, such as seafood. Recommended daily iodine intake is 150 μg in adults who are not pregnant or lactating. Ingestion of iodine or exposure above this threshold is generally well-tolerated. However, in certain susceptible individuals, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
363
0
18

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 470 publications
(404 citation statements)
references
References 75 publications
5
363
0
18
Order By: Relevance
“…It showed that median Tg appeared to follow a U-shaped curve with the nadir at an UIC of 100-300 lg/L. When iodine intake is very high, excess iodide transiently inhibits the activity of thyroid peroxidase and proteolysis of Tg, which subsequently reduces the synthesis and secretion of thyroid hormones (i.e., the Wolff-Chaikoff effect) (87). However, when prolonged excess iodine intake occurs, Tg could increase because the thyroid gland fails to escape from the Wolff-Chaikoff effect (88).…”
Section: Childrenmentioning
confidence: 99%
“…It showed that median Tg appeared to follow a U-shaped curve with the nadir at an UIC of 100-300 lg/L. When iodine intake is very high, excess iodide transiently inhibits the activity of thyroid peroxidase and proteolysis of Tg, which subsequently reduces the synthesis and secretion of thyroid hormones (i.e., the Wolff-Chaikoff effect) (87). However, when prolonged excess iodine intake occurs, Tg could increase because the thyroid gland fails to escape from the Wolff-Chaikoff effect (88).…”
Section: Childrenmentioning
confidence: 99%
“…6 Iodine toxicity can develop when consuming >1.1 mg daily. 7 In healthy subjects, excessive intake of iodine acutely inhibits thyroid hormone secretion and temporarily inhibits thyroid biosynthesis. After prolonged exposure to excessive iodine, organification and thyroid hormone biosynthesis resume in a normal fashion.…”
Section: Figurementioning
confidence: 99%
“…The washing operation has been repeated twice. At selected intervals (1,2,4,6,8,12,20 and 24 h) 1.5 ml of the dermal bathing solution was removed and collected for the analyses. Each receptor sample was immediately replaced with an equal volume of fresh made physiological solution.…”
Section: The Experimentsmentioning
confidence: 99%
“…In animal experiments, transcutaneous absorption of PI through healthy skin has also been examined using radioisotope I125 (Furudate et al, 1997). In individuals with dysregulation of the thyroid follicular cell, excess iodine exposure can induce thyroid dysfunction, which might be transient or permanent (Leung and Braverman, 2014). The aim of our study was to calculate the skin absorption of iodine after the application on the skin of povidone-iodine solution used by health care workers during surgical procedures.…”
Section: Introductionmentioning
confidence: 99%